Cystic Fibrosis Bone Disease: The Interplay between CFTR Dysfunction and Chronic Inflammation - Óscar Fonseca; Maria Salomé Gomes; Maria Adelina Amorim; Ana Cordeiro Gomes (Biomolecules, 2023)
Cystic fibrosis is a monogenic disease with a multisystemic phenotype, ranging from predisposition to chronic lung infection and inflammation to reduced bone mass. The exact mechanisms unbalancing the maintenance of an optimal bone mass in cystic fibrosis patients remain unknown. Multiple factors may contribute to severe bone mass reduction that, in turn, have devastating consequences in the patients’ quality of life and longevity. Here, we will review the existing evidence linking the CFTR dysfunction and cell-intrinsic bone defects. Additionally, we will also address how the proinflammatory environment due to CFTR dysfunction in immune cells and chronic infection impairs the maintenance of an adequate bone mass in CF patients.